Finding our way: secured transactions and corporate bankruptcy law and policy in America and England. Issue 2 (3rd July 2018) - Paterson, Sarah
ABSTRACT: This article is concerned with debate in England as to whether English law has tipped too far in favour of promoting corporate bankruptcy law's policy concerns to the detriment of an effective secured transactions law regime, and debate in America as to whether reform to secured transactions law has tipped too far in favour of secured transaction law's policy concerns to the detriment of an effective corporate bankruptcy regime. Through a detailed analysis of the evolutionary history of secured transactions and corporate bankruptcy law and policy in both America and England, the article analyses why each jurisdiction approaches balancing the policy objectives in a fundamentally different way, and the role which the very different institutional environments in corporate bankruptcy have played in mediating between them. It argues that this legal and institutional evolutionary history suggests relatively modest ongoing reform in both jurisdictions, closely adapted to local conditions.